2022
DOI: 10.1039/d2ob01496c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel all-hydrocarbon cross-linked aza-stapled peptides

Abstract: Novel all-hydrocarbon cross-linked aza-stapled peptides were designed and synthesized by ring-closing metathesis between two aza-alkenylglycine residues. Three aza-stapled peptidic analogues based on the peptide dual inhibitor of p53-MDM2/MDMX interactions were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The conformational preferences of azaamino acid residues have been studied theoretically [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and experimentally [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The results showed that the preferred dihedral angles of the backbone of these azaamino acid residues are in the range of ϕ = ±90° ± 30°, ψ = 0° or ±180° ± 30°, which is appeared to be the polyproline II (β P ), and β-turn motif (α R , α L , δ R , or δ L conformation) [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conformational preferences of azaamino acid residues have been studied theoretically [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and experimentally [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The results showed that the preferred dihedral angles of the backbone of these azaamino acid residues are in the range of ϕ = ±90° ± 30°, ψ = 0° or ±180° ± 30°, which is appeared to be the polyproline II (β P ), and β-turn motif (α R , α L , δ R , or δ L conformation) [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%